Hydrogenation of monolayer molybdenum diselenide via hydrogen plasma treatment. Issue 43 (21st August 2017) - Ma, Kyung Yeol; Yoon, Seong In; Jang, A-Rang; Jeong, Hu Young; Kim, Yong-Jin; Nayak, Pramoda K.; Shin, Hyeon Suk
Abstract : We report a simple and effective method for hydrogenation of monolayer MoSe2 using hydrogen plasma treatment. Abstract : Functionalization of transition metal dichalcogenides has been studied with the aim of tuning their electrical and optical properties, but structural information during functionalization and its reversibility have not been elucidated. We report a simple and effective method for hydrogenation of monolayer MoSe2 using hydrogen plasma treatment. The covalent bonding of hydrogen to MoSe2 was confirmed by X-ray photoelectron spectroscopy, and the degree of hydrogenation was modulated from 32% to 80% by increasing the plasma treatment time from 5 to 40 s. Transmission electron microscopy confirmed a 1.5% reduction in the lattice constant of hydrogenated MoSe2 without structural damages or defects; crystal structures of hydrogenated MoSe2 and as-prepared MoSe2 were identical. Photoluminescence (PL) investigation of hydrogenated MoSe2 showed charge transfer from hydrogen to MoSe2 . Furthermore, reversible desorption of hydrogen from hydrogenated MoSe2 was achieved by heat treatment. The optical and electrical properties of as-prepared and hydrogenated MoSe2 samples were compared. The PL peak of hydrogenated MoSe2 returned to the as-prepared one after heat treatment at 500 °C. Furthermore, the electron mobility of MoSe2 decreased from 29 to 9 cm 2 V −1 s −1 after hydrogenation and was restored to 27 cm 2 V −1 s −1 upon heat treatment at 500 °C. This reversible hydrogen adsorption and desorption lends control over the optical and electrical properties of monolayer MoSe2 and contributes to the hydrogen functionalization of monolayer transition metal dichalcogenides and other two-dimensional materials.